Tradition of Giving Palangkahan Money in Marriage in Lima Puluh Kota Regency - Asari Mista Mira; Hendri Hendri; Sofia Ridha; Muhammad Ridha; Andriyaldi Andriyaldi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This research explores the tradition of palangkahan money in marriage practices in Nagari Lubuak Batingkok, Lima Puluh Kota Regency. The objective of this study is to examine the cultural and social significance of the tradition, focusing on its role in family relationships and its alignment with Minangkabau customs. A qualitative methodology was employed, using interviews and field observations with local adat leaders, community elders, and knowledgeable informants. The findings reveal that palangkahan money is not just a financial exchange but a symbolic gesture intended to maintain emotional harmony between siblings, particularly when the younger sibling marries before the older one. The amount of palangkahan money is flexible, varying according to family agreements and the economic capabilities of the parties involved. This adaptability is crucial in maintaining the tradition's relevance in modern times. The study concludes that the tradition of palangkahan money plays a significant role in preserving cultural values, fostering mutual respect, and ensuring family harmony. It also highlights the interaction between Minangkabau cultural norms and Islamic teachings, showing how the practice adapts to contemporary religious and social frameworks. The academic contribution of this study lies in offering a nuanced perspective on how local customs persist and evolve within the context of modern social dynamics. The research also underscores the importance of qualitative fieldwork in capturing the lived experiences of individuals within a specific cultural context.